Post-Divorce Consequences: A Legal Study of Decision No. 1442/Pdt.G/2018/PA.Btl - Arifia, Ayu Yustika; Lestari, Ahdiana Yuni (Media of Law and Sharia, 2025)
Marriage is a union formed between a man and a woman legally. However, divorce often brings various challenges, one of which is the issue of child custody when children are born into the marriage. The research examines who is granted custody of the child in case No. 1442/Pdt.G/2018/PA.Btl and the responsibilities of parents after divorce based on the same case ruling. The study aims to determine the legal custody arrangement as per the verdict in case No. 1442/Pdt.G/2018/PA.Btl and how parental responsibilities are implemented post-divorce. The research employs an empirical normative legal approach. The study's findings reveal, custody is implicitly granted to the mother, as the child is still a minor (under 12 years old) and had been living with the mother prior to the divorce. Moreover, the responsibilities of divorced parents align with Article 41 of Law No. 1 of 1974 on Marriage and Article 104(1) of the Compilation of Islamic Law (CIL), which state that both parents remain obligated to care for and educate their child, with the father responsible for covering the child's living and educational expenses